SPOTIFY APPLICATION AS A MEDIUM TO IMPROVE THE STUDENTS’ LISTENING ABILITY - Asmi Dwicahya cahya; Yuspar Uzer; Noviati (Universitas PGRI Palembang, 2024)
The advent of digital technology has revolutionized various sectors, including education, by providing automated and sophisticated systems to enhance learning experiences. This study explores the effectiveness of the Spotify application as a medium to improve students' listening abilities in English. Recognizing the significance of listening as one of the four essential language skills, this research addresses the challenge students face in mastering listening due to limited vocabulary and noisy classroom environments. Utilizing a pre-experimental design with a quantitative approach, this study involved pre-test and post-test assessments of two groups: a control class and an experimental class using the Spotify application. The research instrument consisted of written tests, including fill-in and multiple-choice formats, designed to measure students' listening performance. Data collection focused on comparing pre-test and post-test scores to evaluate improvements. The findings revealed a significant enhancement in students' listening abilities after using the Spotify application, with mean scores increasing from 42.89 to 82.42, reflecting a 39.52% improvement. The t-test value further supported these results (5.72 > 2.026). The study concludes that Spotify, with its diverse features such as music discovery, personalized playlists, lyrics integration, and offline access, serves as an effective tool to engage students and improve their listening skills. This method not only addresses the difficulties students face in listening but also motivates them through an enjoyable and interactive learning process.